A phenomenological approach to superconductivity and the learning processes of students - Michelini, Marisa; Stefanel, Alberto (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
Superconductivity is an important part of modern physics. Its discussion in school connects with that of electromagnetism, allowing experimental exploration aimed at the construction of phenomenological laws, describing it. In the framework of the Model of Educational Reconstruction, an educational path in vertical perspective was designed. It pass from the exploration of Magnetic and Electric Properties of Materials, to the construction of phenomenological laws, describing the superconducting state. Research experiments, conducted with more than 300 students from High Schools and monitored with the use of tutorials and pre / post questionnaires, document positive learning paths, in which the peculiar properties of superconductors are more often correlate each Other in models based on electromagnetism, rather than remain separate descriptors of phenomena.